PENGARUH INTELLECTUAL CAPITALTERHADAP KINERJA KEUANGAN PERUSAHAAN DENGAN CORPORATE GOVERNANCESEBAGAI VARIABEL MODERASI: Studi Kasus Pada Perusahaan Manufaktur Sektor Aneka Industri DiBursa Efek Indonesia Periode 2017-201 (STIE Rajawali Purworejo, 2021)
Intellectual capital is the sum of what is produced by three main things in an organization, namely capital employed, human capital and structural capital which are related to knowledge and technology to provide added value for the company in the form of competitive advantage. This research aims to analyze